Optimization of banana juice extraction by combining hot water treatment, citric acid and pectinase - Tanvir Ahmed Laskar; Abhinab Boruah; Mohit Singla; Nandan Sit (Future Postharvest and Food)
Abstract This study focuses on optimizing the extraction of Bhim Kol banana juice using a combined approach of enzymatic extraction, hot water treatment, and citric acid concentration. Bhim Kol bananas are recognized for their distinctive flavor and nutritional richness; however, their dense pulp and thick peel pose challenges for traditional extraction methods. The research seeks to improve juice yield, flavor retention, and nutritional content by investigating the synergistic effects of enzymatic extraction, hot water treatment, and citric acid. Hot water treatment durations of 0, 20, and 40 min, Pectinase concentrations of 0, 0.4%, and 0.8%, and citric acid concentrations of 0, 0.1%, and 0.2% were explored. Experiments are designed according to the Box–Behnken design to determine optimal processing conditions. The outcomes reveal that under optimal conditions, 36.548 min of hot water treatment, 0.80% pectinase concentration, and 0.20% citric acid concentration, a 62% juice yield was achieved. This is accompanied by attributes such as clarity (0.878), lightness (L) value of 30.364, total soluble solids of 20.5°B, reducing sugar content (15.126%), viscosity (4.288 mPa.s), acidity (0.268%), and pH (4.256), respectively. These findings have practical implications for the banana processing industry, offering insights into sustainable and cost‐effective methods for extracting Bhim Kol banana juice.